Comparing the Effectiveness of Mindfulness-Based Cognitive Behavioral Group Therapy and Psychodrama on Distress Tolerance and Anxiety Sensitivity in Bereaved Survivors of Deceased COVID-19 Patients - Karaminezhad , Javid; Nori, Ali; Asgari , Mohammad (KMAN Counseling & Psychology Nexus, 2026)
The objective of this study was to compare the effectiveness of mindfulness-based cognitive behavioral group therapy and psychodrama on distress tolerance and anxiety sensitivity among bereaved survivors of patients who died due to COVID-19. This applied, quasi-experimental study employed a pretest–posttest control group design with a two-month follow-up. The population consisted of bereaved survivors of deceased COVID-19 patients in Shiraz, Iran. Thirty-six eligible participants were selected through purposive sampling and randomly assigned to a mindfulness-based cognitive behavioral therapy group, a psychodrama therapy group, or a control group (12 participants per group). The interventions were delivered in group format over eight and ten 90-minute sessions respectively. Data were collected at pretest, posttest, and follow-up using the Distress Tolerance Scale and the Anxiety Sensitivity Index-Revised. Statistical analysis was conducted using repeated-measures ANOVA and Bonferroni post-hoc tests in SPSS-22. Repeated-measures ANOVA revealed significant main effects of time and significant interaction effects between time and group for all components of distress tolerance and anxiety sensitivity (p < .001). Between-group comparisons indicated significant differences across all outcome variables (p < .001). Bonferroni post-hoc analyses demonstrated that both intervention groups significantly outperformed the control group, while the psychodrama group showed significantly greater improvement than the mindfulness-based cognitive behavioral therapy group on all components (p < .05). Treatment gains were maintained at follow-up. Both mindfulness-based cognitive behavioral therapy and psychodrama effectively enhanced distress tolerance and reduced anxiety sensitivity in bereaved COVID-19 survivors, with psychodrama producing superior and more durable outcomes.